Penentuan Rute Distribusi LPG menggunakan Teknik Simulated Annealing pada PT XYZ - Mutia Kanzha Putri Santoso; Halimah Anis Kurlillah; Purwanti Purwanti; Adelia Tata Anggita; Naufal Syauqi Bimadhieka Nk; Nenzy Agustin Dwi Prahesti (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
This study aims to determine the optimal LPG gas distribution route where the distance traveled becomes closer so that it will minimize transportation costs and in terms of time make the distribution more efficient. The route uses the location of 7 bases that will be addressed by agents from PT XYZ in distributing LPG gas. This practical work took place from February to March 2024. The method used in relation to this route problem is Simulated Annealing where as iterations increase, the algorithm will tend to reject poor solutions. Thus, the graphical results will show a gradual decrease in fitness value towards a more optimal solution. The results of this practical work show that the use of the Simulated Annealing method is feasible in finding the optimal route. This method produces a final route with a distance of 50.8 km to 49.3 km with a travel route from PT XYZ- PG. Agus A LPG- PG. LPG Store Mr. Tri- PG. LPG Pertamina Bp. Didik- PG. LPG Budi- PG. LPG Pertamina Sunarno- PG. LPG Sugiman- PG. Lasmini LPG until returning to PT XYZ.